College Activity e-Book System and Residency Notification using Mobile Networking(CABS-RN) - Noor Fadhlihana, Muhamad Asral; Suriati Khartini, Jali; Mohamad Imran, Bandan; Noralifah, Annuar (2012)
The integration between web-based systems with Short Message Service (SMS) has been widely applied in various fields for instance business application, educational purposes and management system. Furthermore, the integration has enhances information management efficiency, as well as improves the quality of communication distribution and well-informed knowledge of interest. This paper focuses on the development of a web-based system using mobile networking, with integration of SMS into college web-based system. For the preliminary study, it covers the computerization of current college book system focusing on how to calculate student’s merit point, as the upcoming semester residential placement for students will be based on their cumulative merit points. In this paper we introduce CABS-RN prototype and the result of the CABS-RN is discussed. The implementation of CABS-RN took place at one of Universiti Malaysia Sarawak (UNIMAS) residential colleges, Kolej Tun Ahmad Zaidi (TAZ).